Collisional thermalization of minor ions in the solar wind - E. Johnson; B. A. Maruca (Frontiers in Astronomy and Space Sciences)
IntroductionAs the solar wind transits through the heliosphere, Coulomb collisions among constituent particles drives it toward local thermodynamic equilibrium. Prior studies of ion collisions in the solar wind have focused on the two most abundant solar wind ions: protons (ionized hydrogen) and α-particles (fully ionized helium).MethodsSome of the studies have used the technique of collisional analysis to incorporate the effects of collisions and expansion, to extrapolate the evolution of solar-wind ion temperature ratios. This study is the first to apply collisional analysis to the minor ions in the solar wind: carbon, oxygen and iron. Observations of ion temperature ratios in the near-Earth solar wind (r = 1.0 au) are used to predict their values closer to the Sun (r = 0.1 au).ResultsIon measurements from the Advanced Composition Explorer (ACE) mission were used as individual boundary conditions for the equations of collisional analysis, which were solved numerically to make predictions of the temperature ratios. By using a large dataset spanning twelve years, the distributions of ion temperature ratios measured at r = 1.0 au can be compared to those predicted at r = 0.1 au.DiscussionThe predicted distributions suggest that the ratio of minor-ion temperatures to that of protons is significantly higher closer to the Sun, which is consistent with expectations for a zone of preferential minor-ion heating in/near the solar corona.